READINESS TO ADOPT QRIS AMONG MSMES IN SAMARINDA: AN EMPIRICAL ANALYSIS - Wulansari, Kristin; Shoimah, Siti; Agustiningtyas, Eka; Suryadi, I Gede Iwan; Rahajaan, Thomas Evi Viktor (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2024)
Quick Response Code Indonesian Standard (QRIS), developed by Bank Indonesia and the Indonesian Payment System Association, is a versatile payment system that accepts transactions from both bank and non-bank sources. Given the increasing competitive business environment and the necessity for efficient and swift payment systems, Micro, Small, and Medium Enterprises (MSMEs) need to be prepared to adopt QRIS. This study aims to assess the readiness of MSMEs in Samarinda to implement QRIS. The research employs the Technology Acceptance Model (TAM) with the inclusion of a trust variable. Primary data were collected from 220 respondents and analyzed using AMOS. The study examines six variables: trust, perceived usefulness, perceived ease of use, attitude, behavioral intention, and adoption system. Eight hypotheses were tested, all showing significant effects: trust on perceived ease of use, trust on perceived usefulness, perceived ease of use on perceived usefulness, trust on attitude, perceived ease of use on attitude, perceived usefulness on attitude, attitude on behavioral intention, and behavioral intention on the adoption system. The findings suggest that the readiness of MSMEs to adopt QRIS is crucial for accelerating national economic recovery post-COVID-19, particularly for MSMEs in Samarinda. The adoption of QRIS is expected to enhance the efficiency and effectiveness of payment systems, contributing to the overall growth and competitiveness of MSMEs.